Connectors for electrical and electronic equipment. Rectangular connectors. Detail specification for 8-way, shielded, free and fixed high density connectors for data transmission with frequencies up to 100 MHz and with current carrying capacity up to 1 A Part 01, (17th July 2020) - British Standards Institution,
No abstract available